2001
DOI: 10.1055/s-2001-16606
|View full text |Cite
|
Sign up to set email alerts
|

Exposure of the Petrous Segment of the Internal Carotid Artery Through the Extradural Subtemporal Middle Cranial Fossa Approach: A Systematic Anatomical Study

Abstract: The relationships between the horizontal segment ofthe internal carotid artery (ICA) The horizontal segment of the petrous in-ticular, the relationship among the structures of the ternal carotid artery (ICA) can be exposed through petrous apex must be understood. We performed a the extradural subtemporal middle cranial fossa ap-systematic anatomical study to determine a safe proach,116 which requires good knowledge of the and effective method for exposing the ICA anatomy of the petrous apex.1,2,5-8l10l2-15,1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 16 publications
1
15
0
2
Order By: Relevance
“…20 The greater superficial petrosal nerve originating from the anterior aspect of the geniculate ganglion usually travels anteromedial above the genu and the horizontal segment of the IICA. 20 23 ; others, shorter lengths 22,24,25 ; and others, longer lengths. 21 The diameter of the IICA was constant in all of its 3 segments, being measured at 5.20 mm (range, 4.00-8.00 mm).…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…20 The greater superficial petrosal nerve originating from the anterior aspect of the geniculate ganglion usually travels anteromedial above the genu and the horizontal segment of the IICA. 20 23 ; others, shorter lengths 22,24,25 ; and others, longer lengths. 21 The diameter of the IICA was constant in all of its 3 segments, being measured at 5.20 mm (range, 4.00-8.00 mm).…”
Section: Resultsmentioning
confidence: 97%
“…20 Other authors reported similar data. 21,23,24 Since the seminal studies of Glasscock and Paullus, numerous studies have dealt with the surgical management of skull base lesions involving the IICA via the middle fossa approach or its variants. The complex anatomy of this area led to the definition of geometrical landmarks such as the Glasscock triangle and the middle fossa rhomboid for guiding the approach to these lesions while minimizing possible neurovascular complications.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Measurements reported in middle fossa approach anatomic studies and radiologic studies [20][21][22] are shown and compared in Table 1.…”
Section: Discussionmentioning
confidence: 99%
“…The horizontal portion of the internal carotid artery (ICA) may be exposed by drilling the bone just inferomedial to the GSPN (Fig. 4b), but may be dehiscent in 20-63% of cases [6,50,53].…”
Section: Anterior Petrosectomymentioning
confidence: 99%